Does the Use of Robotic Technology Improve Outcomes in Primary Total Hip Arthroplasty? - Dzhavadov, Alisagib A.; Dikmen, Goksel; D'Apuzzo, Michele R.; Yeo, Seng Jin; Zagra, Luigi; Bilgen, Omer Faruk; Caliskan, Emrah; Mont, Micheal A.; Parvizi, Javad; Tuncay, Ibrahim (CHURCHILL LIVINGSTONE INC MEDICAL PUBLISHERS, 2025)
World Expert Meeting in Arthroplasty, Istanbul, TURKEY, AUG 30-31, 2024
Keywords: robotic surgery; hip; arthroplasty; outcome; complication; conventional